Effect of planting date in productivity of Nigella sativa L. and quality of essential oil extracted from them in the south of Hama area (Damascus University Journal of agriculture sciences, 2024)
The experiment was carried out in the village of Ghor Al-Asi, located in the south of Hama Governorate, during the agricultural season (2016-2017) according to the design of the factorial experiments in order to study the effect of planting date in the growth and productivity of the Nigella Sativa crop and the quality of the essential oil extracted from it. Sowing was done on two different dates (15 December and 15 January)The results of the research showed that to obtain the best production of the essential oil and the percentage of the active substance, it is recommended to use the early planting date (December).
Keywords: Nigella sativa, planting date, productivity; essential oil; thymoquinone